Study on corollary of seismic base isolation system on buildings with soft storey - Saiful Islam, A.B.M.; Jameel, M.; Ahmad, Syed Ishtiaq; Jumaat, Mohd Zamin (International Journal of Physical Sciences, 2011)
Soft storey buildings are characterized by having a storey which has a lot of open spaces. This soft storey creates a major weak point in an earthquake. Since soft stories are classically associated with retail spaces and parking garages, they are often on the lower stories of a building, which means that when they collapse, they can take the whole building down with them, causing serious structural damage which may render the structure totally unusable. In this study, efforts have been given to examine the effect of incorporation of isolator on the seismic behavior of buildings subjected to the appropriate earthquake for medium risk seismicity region. It duly ensures incorporating isolator with all relevant properties as per respective isolators along with its time period and damping ratio. Effort has also been made here to build up a relationship for increasing storey height and the changes for incorporating isolator with same time period and damping ratio for both lead rubber bearing (LRB) and high damping rubber bearing (HDRB). Dynamic analyses have been carried out using response spectrum and time history analysis. Behavioral changes of structural parameters are investigated. The study reveals that the values of structural parameters reduce a large amount while using isolator. However, LRB is found beneficial than HDRB. The structure experiences huge storey drift at the soft storey level that may be severe and cause immature failure. The amount of masonry infill is very vital for soft storey buildings as its decrement increases reasonable displacements.